2020
DOI: 10.1108/apjml-08-2019-0495
|View full text |Cite
|
Sign up to set email alerts
|

Impulse buying in social commerce: bundle offer, top reviews, and emotional intelligence

Abstract: PurposeConsidering the rapid adoption of social media among consumers and organizations, this study intends to examine the impact of online bundle promotions and contextual interactions on impulse buying as consumers encounter them synchronously. Hence, a research model is proposed with the integration of perceived transaction value, perceived acquisition values, top reviews information, impulse buying tendency and emotional intelligence following the stimulus-organism-response framework, promotional framing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 115 publications
5
40
0
Order By: Relevance
“…This also showed that the majority of tweets were made by a very small percentage of users, which was backed by the centrality analysis of the network diagram. The first 9% of the users accounted for 56% of the tweets, which is consistent with previous studies ( Zafar et al 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…This also showed that the majority of tweets were made by a very small percentage of users, which was backed by the centrality analysis of the network diagram. The first 9% of the users accounted for 56% of the tweets, which is consistent with previous studies ( Zafar et al 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Unlike in the past, consumers do not only receive product information, but they also generate and distribute information based on their preferences and experiences, provide recommendations, and interact with product or service providers ( Khokhar et al., 2019 ). These actions enhance consumption behaviour in terms of impulse buys ( Zafar et al., 2020 ), as well as lead to the generation of food waste ( Sainsbury's, 2016 ). In addition, behaviours around food waste are associated with neurotic behaviour and environmental conditions ( Boeve-de Pauw et al., 2011 ; Milfont and Sibley, 2012 ; Opayemi et al., 2020 ).…”
Section: Conceptual Background and Development Of Hypothesesmentioning
confidence: 99%
“…Consumers' decision [5], [19] N N N N N [7], [11], [13], [14], [15], [18], [21], [28] Y N N N Y [8], [9], [6], [16], [10], [34], [35] Y N N N N [42], [45], [46], [47] Y N N N N [20], [39], [40], [48] Y…”
Section: Supply Chainmentioning
confidence: 99%
“…Another study on impulsive consumption argued that such behavior reduces environmental sustainability [46]. Zafar et al [47] also declared that online influencer-consumer interactions lead to impulse spending by consumers.…”
Section: Models and Equilibrium Solutionsmentioning
confidence: 99%